Women in science: myth, harsh reality, or advantage - Feldman, Ruth (Frontiers in Human Neuroscience, 2023)
We begin with Gerald Edelman's definition: "Science is imagination in the service of the verifiable truth", which underscores "verifiability", truth reached by evidence, as the pathway science charts to Truth. "Verifiability" is named after the Roman Goddess Veritas, the daughter of Cronos and the mother of Virtus, suggesting that mythology viewed science as embodied by a female, embedded in historical time, and aimed to breed values. We contemplate three perspectives on the topic. The Veracity Perspective holds that science is impartial to the gender, race, political camp, or religious affiliation of its practitioner and from this perspective "women in sciences" is an oxymoron; science is, essentially, genderless. We argue that this perspective is misleading. Becoming a scientist requires education, resources, encouragement, time, and funding, and the lack of such provisions banned women from the gates of Truth. The Harsh Reality perspective presents a grim picture. Only 3.6% of Nobel Prizes in sciences were awarded to women and percentages of women in top academic positions are a third or lower across the US and Europe. We contemplate internal and external reasons for this reality. The Potential Advantage position asks whether women may have unique sensitivities to cumulative knowledge. We discuss 20th century philosophical models that call to move from the metaphysical to the daily in the acquisition of knowledge and on research on neural pathways to motherhood and fatherhood. We conclude by highlighting the emergence of novel topics in neuroscience; interaction synchrony, inter-brain communication, and social and affiliative neuroscience.